Role of the Neurotransmitter Reuptake-Blocking Activity of Antidepressants in Reversing Chloroquine Resistance In Vitro in Plasmodium falciparum - Taylor, Dale (American Society for Microbiology, 2000)
Since the discovery of the chloroquine (CQ) resistance reversal properties of several different, structurally unrelated classes of compounds, including antidepressants, the way is again open to employ the aminoquinoline drugs to combat malaria effectively. In this study, CQ sensitivity was restored to varying extents in vitro in the CQ-resistant Plasmodium falciparum strain RSA11 by using the antidepressants amitriptyline, citalopram, oxaprotiline, and nomifensine. The 50% inhibitory concentrations (IC(50)) of CQ were reduced from 360 to as low as 11 nM when antidepressants were present. These particular antidepressants are highly specific for blocking the ATP-binding cassette transport protein-mediated reuptake of different neurotransmitters at the synaptic level. This study was aimed at determining the extent to which the neurotransmitter reuptake-blocking properties of these antidepressants play a role in the reversal process. None of the compounds or CQ-antidepressant combinations tested had innate antimalarial activity. No chemosensitizer or combination showed an increased CQ accumulation or significant shift in the IC(50) in the CQ-sensitive clone D10. Of the compounds tested, citalopram, a highly specific serotonin reuptake blocker, produced the largest shift observed in the IC(50) for the resistant isolate RSA11. No particular class of antidepressant was found to be better than any other at restoring CQ sensitivity. We conclude that the resistance-reversing properties of these compounds do not correlate with their activities as reuptake blockers.